Acupuncture combined with multiple therapies for angina pectoris: a systematic review and network meta-analysis - Kong, Xiangyu; Gu, You; Qiu, Zhao (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveAcupuncture combined with multiple treatment modalities has been widely employed for treating angina pectoris. This paper compared the efficacy of acupuncture combined with multiple treatment modalities for angina pectoris by network meta-analysis (NMA).MethodsAs of November 2023, this study searched eight electronic databases for randomized controlled trials (RCTs) of acupuncture combined with multiple modalities for the treatment of angina pectoris based on antianginal therapies. Primary efficacy indicators included the number of angina episodes and duration of episodes, and secondary indicators included clinical efficacy based on symptom improvement and electrocardiographic efficacy based on ST-segment and T-wave improvement. The Cochrane Risk of Bias tool 2.0 (RoB 2.0) was used for risk of bias assessment. A random-effects Bayesian NMA was performed using R (version 4.3.1) and Stata (version 16.0).Results46 RCTs were enrolled, with 3976 patients with angina pectoris. In reducing the number of angina episodes, acupuncture [MD: −3.79; 95% CrI (−6.34, −1.31)] and acupuncture + TCM [MD: −3.06; 95% CrI (−5.49, −0.62)] were superior to antianginal therapies, with acupuncture having the best efficacy (SUCRA: 78.2%). In shortening the duration of angina episodes, electroacupuncture (EA) + traditional Chinese medicine (TCM) was the most effective (SUCRA: 95.1%), superior to antianginal therapies [MD: −5.04; 95% CrI (−9.18, −0.89)], adjunctive therapy [MD: 7; 95% CrI (1.58, 12.39)], rehabilitation therapy [MD: −5.38; 95% CrI (−10.75, −0.05)], and warm acupuncture + adjunctive therapy [MD: −6.71; 95% CrI (−13, −0.48)]. In terms of clinical efficacy, thumbtack needling had the best efficacy (SUCRA: 82.1%), superior to TCM [RR: 1.3; 95% CrI (1.02, 1.69)] and antianginal therapies [RR: 0.75; 95% CrI (0.6,0.91)]. In electrocardiographic efficacy, EA showed the best efficacy (SUCRA: 92.9%), superior to antianginal therapies [RR: 0.52; 95% CrI (0.35, 0.71)] and acupuncture [RR: 0.62; 95% CrI (0.39, 0.91)].ConclusionAcupuncture performs best in reducing anginal episodes; EA + TCM is the most effective in shortening the duration of anginal episodes; thumbtack needling is the most effective in clinical efficacy; and EA shows optimal results in electrocardiographic efficacy. To further validate these findings, multicenter and large-sample RCTs are needed.Systematic Review RegistrationPROSPERO [CRD42024505456].